Protocolo sobre processamento de produtos para saúde na Central de Material e Esterilização do Hospital São Paulo/HU-UNIFESP - Santos, Maria Valdenice Lopes dos [UNIFESP] (2019)
Introduction: The processing of health products comprises a set of actions that begins with the receiving of the contaminated product, proceeds with its cleaning, disinfection, drying, visual inspection, and evaluation of its integrity and functionality, and ends with the preparation (assembly and sterilization), storage, transportation, and distribution of the product. Because of the complexity of the service, the development of a protocol that provides guidance and optimizes resources can ensure the quality and safety of materials for health services. Objective: To develop and validate a protocol for processing health products at the Material and Sterilization Center of the São Paulo Hospital/HU-UNIFESP. Method: This descriptive study on the development of a protocol was performed in steps, beginning with a literature review, content production, and validation using the Delphi technique. The content validity index (CVI) was used to measure expert agreement based on questionnaire responses. Results: A protocol was developed based on the literature and institutional characteristics. After the second round of consultation using the Delphi Technique, the overall CVI was 1.0, corresponding to 100% consensus among experts, and therefore above the minimum CVI of 0.90 required for validation. The final version of the validated protocol has 45 pages, 8 sections, 32 sub-subsections, and 20 illustrations. Conclusion: The Protocol for Processing Health Products at the Material and Sterilization Center of the São Paulo Hospital/HU-UNIFESP was developed and validated.